(untitled) (Educological discourse, 2015)
The article deals with a presentation of a category of good-doing that is briefly explored in modern pedagogics of the primary school. The priority task was to clarify the essence of the concept of " good-doing" and its interpretation in the context of teaching the age features of younger schoolchildren’s the definitive analysis of the concept of "good-doing of junior students" is indentified; the structural-component analysis of good-doing of younger schoolchildren is implemented and the criteria, indicators of formation of personal education are indentified. Prospects for further study of the problem is the research of levels of development of good-doing of younger students based on the selected criteria.